Keuangan Syariah dalam Menghadapi Resesi Global - Hairun Nisa; Itsnaini Chusnul Khotimah; Hidayani; Darsi Ahmadan (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2024)
This research aims to investigate the development, role, principles and mechanisms of Sharia finance so that they can be applied in facing the global financial crisis. The research used in this research is library research, using a descriptive qualitative approach, namely data obtained from the library and then analyzed descriptively qualitatively. The results of the analysis are that global sharia financial assets have reached US3.96 trillion in 2021. This figure has increased by 16.76% from the previous year, namely US3.39 trillion, which indicates that the global sharia financial industry is growing more resiliently in line with the global economic recovery. Sharia economics and finance also contribute to accelerating the momentum of national economic recovery. The role of sharia financing is increasingly important to support economic growth and stability amidst increasing global uncertainty. Sharia Financial Principles are free from maysir, gharar, usury, haram and falsehood. The impacts that would arise if a recession occurs in Indonesia are: the weakening of the rupiah exchange rate, increasing unemployment, decreasing demand for Indonesian exports, weakening people's purchasing power, and increasing interest rates. Sharia finance in facing the global recession is first, increasing the independence of MSMEs in the future, secondly improving new strategies in building relationships between MSMEs and banks. Third, being able to identify the causes of recession by paying attention to financing that can affect banking health. Fourth, banking must pay attention to capital adequacy to overcome the risk of bad credit. Fifth, increase the value of profit sharing so that people are interested in saving. Key Words:Islamic Finance, global recession.